KEBIJAKAN VIRTUAL TOUR SEBAGAI MITIGASI DAMPAK PANDEMI TERHADAP PARIWISATA DI KOTA SURABAYA - Dandi Darmadi; Katerina - Bataha; Sumainah Fauziah (Jurnal Penelitian Administrasi Publik, 2021)
ABSTRACT The Covid-19 disaster caused the tourism sektor to decline, including the city of Surabaya, for that innovation was carried out to revive it through a virtual tour policy. The research method used is descriptive qualitative research. The data collected is the result obtained through observation, literature study, and existing archives/documents or written literature closely related to the research title. The Research Results Show that the Covid-19 disaster mitigation efforts carried out in the tourism sektor by providing virtual tour facilities have a good impact on the revival of tourism objects that have been closed. The form of mitigation fulfills several principles and strategies stated in the introductory chapter, namely the principles of cost and benefit, involving various parties and producing results. However, this form of virtual tour mitigation only has a good impact on tourism object managers, while in the tourism sektor, other elements also need attention, such as transportation services, UMKM, hotels, and restaurants. Suggestions from the authors should be that in implementing the virtual tour, the manager provides space for UMKM to promote goods and services. Keywords: Pandemic; covid-19; mitigasi; virtual tour